Form Four Science Students' Perceptions of the Quality of Learning Experiences Provided by Assessments in STEM Related Subjects - Meng, Chew Cheng; Idris, Noraini (Asian Journal of Assessment in Teaching and Learning, 2015)
The lagging science and mathematics achievement of Malaysian secondary students in international assessment studies and the decreasing enrollment of science students at secondary school level call for the promotion of Science, Technology, Engineering and Mathematics (STEM) education in our country. One of the preliminary steps that could be taken was to identify the quality of learning experiences provided by assessments in STEM related subjects at the secondary school level. In addressing this concern, this study (which is part of a larger research project) aimed to investigate Form Four Science students' perceptions of the quality of learning experiences provided by assessments in STEM related subjects such as Biology, Chemistry, Physics, Mathematics and Additional Mathematics. A cross-sectional survey research design was used and a sample of 852 Form Four Science students was selected from three categories of secondary schools in Peninsular Malaysia, namely Daily High-Performing (121), Full Boarding High-Performing (168) and Daily Normal (563). The Form Four Science students' perceptions of the quality of learning experiences provided by assessments in STEM related subjects were assessed using a five-point Likert scale questionnaire which was developed based on the STEM Education Quality Framework (2011). The result indicated that the students had positive overall perceptions of the quality of learning experiences provided by assessments in STEM related subjects. In addition, there was no statistically significant difference in the overall perceptions of the quality of learning experiences provided by assessments in STEM related subjects in terms of gender. These results augur well for the promotion of STEM education in our country.